2022
DOI: 10.3390/plants11162181
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Effects of Non-Thermal Plasma on Seed’s Morphology, Germination and Genetics—A Review

Abstract: Non-thermal plasma (NTP) is a novel and promising technique in the agricultural field that has the potential to improve vegetal material by modulating the expression of various genes involved in seed germination, plant immune response to abiotic stress, resistance to pathogens, and growth. Seeds are most frequently treated, in order to improve their ability to growth and evolve, but the whole plant can also be treated for a fast adaptive response to stress factors (heat, cold, pathogens). This review focuses m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 154 publications
0
8
0
Order By: Relevance
“…The effect of wettability increase cannot be excluded, but much more complex action mechanisms of the plasma are discussed in the literature, including modifications in the content and balance of phytohormones, effects on gene expression, activation of the energy metabolism, etc. [ 4 , 5 , 10 , 11 ], which are not entirely understood and should represent the subject of further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of wettability increase cannot be excluded, but much more complex action mechanisms of the plasma are discussed in the literature, including modifications in the content and balance of phytohormones, effects on gene expression, activation of the energy metabolism, etc. [ 4 , 5 , 10 , 11 ], which are not entirely understood and should represent the subject of further research.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled delivery of plasma-generated species, adapted to plant needs at different development stages, is considered to be the key strategy for successful application of plasma in the agriculture field. The prospect of using plasma to stimulate the expression of various genes related to embryonic development, plant growth, resistance to pathogens and tolerance to abiotic stress is emphasized in the review of Leti et al [ 4 ]. Novel findings evidencing changes induced by NTP treatment of seeds at the molecular level are analyzed in detail by Mildaziene et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results reported here for barley plants are in line with recent studies with other plants proving that plasma gives rise to biochemical modifications. These have been attributed to the activation of certain enzymes, the modification of proteins, or the activation of specific growth and gene expression factors. A common hypothesis in these works on barley and other plants is that ROS and RNS plasma species formed on the surface of seeds may diffuse into their interior and affect key molecular mechanisms , involving enzymes, proteins, and other biochemical markers (for a comprehensive account of these recent investigations, see the contribution of recent papers to the topic , ). In a recent work from our group on barley seeds, we have shown that plasma affects the ABA (abscisic acid) growing factor in a similar way to hydrogen peroxide, both treatments leading to an increase in germination rates thanks to the enhanced ROS content .…”
Section: Discussionmentioning
confidence: 99%
“…During the last years, among the large variety of methods utilized to improve seedling and plant growth, the application of low-temperature plasmas has received considerable attention in the scientific literature. Recent reviews on the subject have highlighted the complexity of the biochemical and gene expression effects that can be triggered when treating seeds with plasmas. Also, the diversity of scenarios and variables that must be considered in these studies, including type of plants, characteristics of cold plasmas, or environmental growth conditions. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation